Faktor-Faktor yang Mempengaruhi Penjualan Mobil Sedan di Indonesia dan Memprediksi Penerimaan Pajak Penjualan atas Barang Mewah (PPnBM) Kendaraan Mobil Periode 2013-2017 - Audrey Alviona Ribuna Kaban; Sri Yani Kusumastuti (UIR Press, 2019)
This study aims to examine the effect of previously sales, price of the goods, and price of subtitute goods to sales of sedan car. Independent variables used in this study previously sales, price of the goods, and price of subtitute goods, and prediction of sales tax on luxury goods. Shile the dependent variable in thisstudy was measured using sales of sedan cars the measured of the car unit is succesfully sold every year during in the period 2013-2017. The population in this study amounted to 24 sedan’s companies list on Combined Motor Vehicle Industry (GAIKINDO) during 2013 until 2017. Determination of the sample using purpossive sampling method and obtained a sample of 5 sedan’s companies based on certain criteria. The analysis tool used in the panel and the selected model is fixed effect model. The result show that previous sales has positively effect on the sales of sedan car, price of the goods has positive effect on the sales of sedan car. Meanwhile price of subtitute goods has negative effect on the sales of sedan car.